Evaluasi Strategi Bimbingan Manasik Haji di Tengah Pandemi Covid-19 - Hilman, Fathin Anjani; Hanadiviyah, Hanadiviyah; Fitriyani, Gina (Mabrur: Academic Journal of Hajj and Umra, 2022)
The purpose of this study was to determine the evaluation of the Hajj ritual guidance strategy in the midst of the covid-19 pandemic. The research method used in this research is descriptive qualitative research method. Data was taken using data collection techniques with observations, interviews and documentation related to research. The results of the study revealed that the evaluation of the KBIH did not only conduct evaluation meetings related to the rituals of Hajj, but also extract from the prospective pilgrims the advantages and disadvantages of implementing this guidance. Therefore, the evaluation conducted by KBIH does not only review external and internal factors of the implemented strategy, but also measures performance and takes corrective action.